Free double‐paddle posterior tibial artery perforator flap for hypopharynx reconstruction: A case report and literature review. Issue 7 (21st July 2021) - Fritz, Caroline; Meroni, Matteo; Fritsche, Elmar; Rajan, Gunesh; Scaglioni, Mario F.
Abstract: Microsurgical free tissue transfer is nowadays considered to be one of the main options for head and neck reconstruction. The free posterior tibial artery perforator (PTAP) flap is a well‐known reconstructive technique for local defect coverage in the distal leg, and only recently has been employed for head and neck reconstructions. Being a very thin and pliable flap, with low donor site morbidity and constant anatomy, the PTA perforator‐based flap could be a great alternative to the more commonly‐employed radial forearm free flap (RFFF). The present case report shows a complex head and neck defect coverage by means of a free double‐paddle PTA flap, with a concise literature review of previous PTA flap descriptions in this setting. A 59‐year‐old male patient presented with a hypopharynx leakage after radiotherapy due to hypopharynx carcinoma. Since the patient had an occluded ulnar artery on the left side and an arterial line in the radial artery on the right side, both a RFFF and an ulnar artery perforator (UAP) flap were contraindicated. Moreover, two different cutaneous flaps were needed to reconstruct a 6 × 8 cm 2 defect, one for the reconstruction of the hypopharynx and one for the resurfacing of the neck, since previous surgeries and radiotherapy led to severe fibrosis of the neck. The patient had a BMI of 25.4 kg/m 2, which led us to exclude the anterolateral thigh (ALT) flap because of its thickness. For the forementioned reasons, an unconventional double‐paddle PTAP flap based on two perforator vessels was chosen. Based on two perforators, two skin islands were harvested, building a double‐paddle PTA perforator‐based flap. The proximal skin island was 6 × 7 cm 2 and the distal one was 6 × 4 cm 2 . The larger skin flap was set at the leakage of the hypopharynx. The smaller skin island was used to monitor the survival of the whole flap and for resurfacing the outer side of the neck. The postoperative course was uneventful and at 3 months follow up the reconstructive result was good with no functional drawback. In view of the obtained result, we can consider that the PTA flap might be a reliable alternative to the much widely used RFFF, with a minor donor site morbidity, for delicate head and neck reconstructions.